A Comparison of a Smartphone App and a Wrist-Worn Fitness Tracker for Self-monitoring of Physical Activity by Older and Younger Users - Kupffer, Rebekka; Wutzler, Melanie; Krems, Josef F.; Jahn, Georg (Smart Objects and Technologies for Social Good, 2018)
Wearables capable of monitoring steps are important elements of behavior change interventions to increase physical activity. For intervention studies, there is currently the choice between smartphone apps and fitness trackers for self-monitoring daily steps. We report results from a pilot study, in which younger and older participants experienced both types of devices, rated usability, and performed usability tasks. The fitness tracker, which was operated with a single touch-sensitive button, proved advantageous in subjective and objective usability. The discussion includes further aspects of the choice between smartphone apps and fitness trackers for use in interventions.